The Negative Influence of Turkish Series’ Dubbing on Algerian Adolescents - ABDERRAZAG, Sara Habib; Kazi-Tani, Lynda (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
Recently, the world has become a small village, mainly due to media and its impact on people. In the Arab world, a special attention starts to be given to dubbed serials, the Turkish ones in particular. The latter have influenced the culture of many categories of viewers, including adolescents. Thus, the focal point of this study is to shed light on Algerian Adolescents’ motives for watching Turkish dubbed series and how the latter affect their way of thinking and behaviour. The present paper will mainly highlight the negative effects for it has been noticed that a great change is taking place on the part of Algerian adolescents. To reach this aim and to better explore the situation, a questionnaire will be conducted for a group of adolescents.